testing header
Math Goodies is a free math help portal for students, teachers, and parents.
Free Math
Newsletter
 
 
Interactive Math Goodies Software

Buy Math Goodies Software
testing left nav
Math Goodies on facebook

Math Goodies Blog
Math Forums @ Math Goodies
Math Forums @ Math Goodies
Home | Profile | Active Topics | Members | Search | FAQ
 All Forums
 Homework Help Forums
 Geometry and Trigonometry
 Math

Note: You must be registered in order to post a reply.

Screensize:
UserName:
Password:
Format Mode:
Format: BoldItalicizedUnderlineStrikethrough Align LeftCenteredAlign Right Horizontal Rule Insert HyperlinkInsert EmailInsert Image Insert CodeInsert QuoteInsert List Insert Special Characters Insert Smilie
   
Message:
* HTML is OFF
* Forum Code is ON

Math Symbols
Squared [squared] Cubed [cubed] Square Root [sqrt] Cube Root [cbrt] Pi [pi]
Alpha [alpha] Beta [beta] Gamma [gamma] Theta [theta] Angle [angle]
Degrees [degrees] Times [times] Divide [divide] Less Than or Equal To [less-than] Greater Than or Equal To [greater-than]
Plus Minus [plus-minus] Integral [integral] Sum [sum] Sub 1 [sub-1] Sub 2 [sub-2]
Element Of [element-of] Union [union] Intersect [intersect] Subset [subset] Empty Set [empty-set]

  Check here to subscribe to this topic.
 
   

T O P I C    R E V I E W
gurly691 Posted - 07/14/2011 : 16:36:23
Construct a truth table for the statement.

(p ↔ q) → p


I got this:

p. q. p<->q
T. T. T
T. F. F
F. T. F
F. F. T

But I don't believe it's correct....please help!
2   L A T E S T    R E P L I E S    (Newest First)
the_hill1962 Posted - 07/19/2011 : 15:46:40
Yes, your table of p <--> q is correct.
Now, the original problem was to put that into an implication with -->p
After you do the interactive lesson that Admin referenced, you will see (or maybe already knew) that p-->q has a table of
p q ..p-->q
T T .. T
T 0 .. 0
0 T .. T
0 0 .. T
So using your table of
p q ..p<->q
T T .. T
T F .. F
F T .. F
F F .. T
in the problem (p ↔ q) → p
makes it look like the following:
p q ..(p<->q)
T T ... T
T F ... F
F T ... F
F F ... T
and then taking the list for (p<->q) with what "p" was gives:
(p<->q) --> p
. T ...... T
. F ...... T
. F ...... F
. T ...... F
So, all you have to to is list the values for ?#? below.
T-->T is ?1?
F-->T is ?2?
F-->F is ?3?
T-->F is ?4?
and that will be the values to finish:
p q ..(p ↔ q) → p
T T ..... ?1?
T 0 ..... ?2?
0 T ..... ?3?
0 0 ..... ?4?
Admin Posted - 07/14/2011 : 16:43:28
quote:
Originally posted by gurly691

Construct a truth table for the statement.

(p q) p


I got this:

p. q. p<->q
T. T. T
T. F. F
F. T. F
F. F. T

But I don't believe it's correct....please help!



See our interactive lessons on Logic.

Gisele

Math Forums @ Math Goodies © 2000-2004 Snitz Communications Go To Top Of Page
This page was generated in 0.03 seconds. Snitz Forums 2000
testing footer
About Us | Contact Us | Advertise with Us | Facebook | Blog | Recommend This Page




Copyright © 1998-2015 Mrs. Glosser's Math Goodies. All Rights Reserved.

A Hotchalk/Glam Partner Site - Last Modified 25 Jan 2015